2017
DOI: 10.1073/pnas.1621432114
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution imaging and quantification of plasma membrane cholesterol by NanoSIMS

Abstract: Cholesterol is a crucial lipid within the plasma membrane of mammalian cells. Recent biochemical studies showed that one pool of cholesterol in the plasma membrane is "accessible" to binding by a modified version of the cytolysin perfringolysin O (PFO*), whereas another pool is sequestered by sphingomyelin and cannot be bound by PFO* unless the sphingomyelin is destroyed with sphingomyelinase (SMase). Thus far, it has been unclear whether PFO* and related cholesterol-binding proteins bind uniformly to the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 16 publications
5
58
0
Order By: Relevance
“…Because the particles originate from the plasma membrane, we suspected that they would contain sphingomyelin. To test this idea, we incubated cholesterol-loaded RAW 264.7 macrophages and primary macrophages with [ 15 N]ALO-D4 and [ 13 C]lysenin [a sphingomyelin-binding cytolysin (15)]. 15 N/ 14 N and 13 C/ 12 C nanoSIMS images revealed that macrophage-derived particles were enriched in both 15 N and 13 C ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the particles originate from the plasma membrane, we suspected that they would contain sphingomyelin. To test this idea, we incubated cholesterol-loaded RAW 264.7 macrophages and primary macrophages with [ 15 N]ALO-D4 and [ 13 C]lysenin [a sphingomyelin-binding cytolysin (15)]. 15 N/ 14 N and 13 C/ 12 C nanoSIMS images revealed that macrophage-derived particles were enriched in both 15 N and 13 C ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A linear regression analysis revealed a positive correlation between 15 N and 13 C enrichments (P < 0.0001). 15 N/ 14 N and 13 C/ 12 C scales are multiplied by 10,000. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue sections were coated with 5 nm of platinum and analyzed with NanoSIMS 50L or NanoSIMS 50 instruments [7, 8]. A 16-KeV 133 Cs + beam was used to bombard the sample, and secondary electrons (SEs) and secondary ions ( e.g., 12 C 14 N–, 1 H–, 2 H–, 12 C–, 13 C–) were collected [7].…”
Section: Methodsmentioning
confidence: 99%
“…8 The accumulation of sphingomyelin in the microvilli was recently confirmed by using nanoscale secondary ion mass spectrometry (NanoSIMS) imaging. 9 Kai Simons and colleagues also conducted a detailed study on the lipid composition of apical membrane by using mass spectrometry. 10 They reported that sphingomyelin is enriched in the apical membrane, compared to the whole cell lipids, by physically isolating apical membrane using nitrocellulose membrane.…”
Section: Roles Of Sphingolipids In the Formation Of Apical Membranementioning
confidence: 99%